Rancang Bangun Alat Lux Meter BH1750 Dengan Sensor Jarak HC-SR04 Untuk Uji Kesesuaian Kolimator - Fitri Anindyahadi; Eko Nugroho; Setyo Adi Nugroho (Jurnal Kendali Teknik dan Sains, 2023)
This research is based on the Regulation of the Nuclear Energy Supervisory Agency of the Republic of Indonesia Number 2 of 2018 concerning Conformity Tests for Diagnostic and Interventional Radiology One component that must be tested with a minimum passing standard of ≥ 100 lux at a distance of 100 cm. Data collection is obtained at the Calibration Agency to obtain accurate results. The purpose of this tool, the Lux Meter is equipped with a distance sensor to measure the light intensity of a collimator lamp with an intensity that must be ≥ 100 within a distance of 100 cm from the light source. So, making a tool that can be used to measure the amount of collimator illumination is accompanied by measuring the distance, so that it can ensure the results are in accordance with the limits that have been determined with a Lux Meter equipped with a distance sensor using the BH1750 module and the HC-SR04 module. For testing the tool made, it was compared with a Standard Lux Meter with the HIOKI brand, an average error value of 0.021 at a distance of 50cm, an error of 00.020 at a distance of 100cm, and an error of 0.022 was obtained, while for testing the distance sensor it was compared with a Standard Meter with the FLUKE brand. The average percentage error value is 0.002 at a distance of 50cm, an error of 0.011 at a distance of 100cm, and an error of 0.008 at a distance of 130cm.